The effectiveness of a training program in improving human quality among a sample of female students at Qatar University - Al-Waheibi, Musalam Salim Ali (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to measure the effectiveness of a proposed training program in improving human quality, after testing it on a sample of (25) female students at Qatar University through the pre-application of the scale, and then implementation The human quality improvement program in (14) training sessions during five weeks. The program included nine domains that represent the fields of man’s relationship with what is around him, such as his relationship with the Creator, himself, the other, and the legal system…etc., then a post-measurement was conducted at the end of the program, and after a break of three weeks, the measurement was conducted The follow-up study to assess the survival of the impact of the program on the sample of the semi-experimental study, and by analyzing the data, the researcher reached several results, most notably the achievement of the effectiveness of the program and the survival of its impact.